PENGARUH MEDIA EXPOSURE, DEWAN KOMISARIS, KOMITE AUDIT DAN KEPEMILIKAN ASING TERHADAP ENVIRONMENTAL DISCLOSURE - Laurentius Richard; Hendra Wijaya (Universitas Katolik Widya Mandala Surabaya, 2022)
Corporate responsibility is a matter of concern to stakeholders and the community. Therefore, companies are encouraged to disclose their responsibilities. In this study, researchers will examine what things will affect and do not affect the company's environmental responsibility. This study aims to analyze the effect of media exposure, board of commissioners, audit committee, foreign ownership on environmental disclosure. The analytical technique used in this research is multiple regression analysis. The object that will be examined in this research is a manufacturing company listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period, and by using purposive sampling as a sample. The results of this study indicate that media exposure and the board of commissioners have a positive effect on environmental disclosure, and this study also shows that the audit committee and foreign ownership have no effect on environmental disclosure.